Incident Number of Decline in Functional Physical Activity In The Elderly at Jebres, Surakarta - Mutnawasitoh, Asita Rohmah; Mirawati, Dita; Cahyaningrum, Hapsari; Setiawan, Cahyo; Sari, Apriliyan Yunita; Azizah, Qoriq Nur; Alvin, Nadia (Universitas Tribhuwana Tunggadewi, 2025)
Health services for the elderly group need to be carried out according to their needs. To understand the health needs of the elderly group, it is necessary to examine the number of cases or prevalence of a case that is a problem for the elderly. Decreased physical functional activity in the elderly is a problem that is often encountered and due to degenerative diseases. Decreased physical functional activity in the elderly results in an increased risk of disability. There have been no reports regarding the number of cases of the elderly who experience decreased physical functional activity, the number of cases or prevalence of decreased physical functional activity in the elderly. The study used descriptive quantitative research method with a cross-sectional research design. The subjects of the study were elderly people aged 60-70 years who had no history of musculoskeletal injury/trauma and did not use walking aids. The research instrument used to measure the decline in functional activity was the Physical Activity Scale for the Elderly (PASE). The assessment results showed that 46 elderly people (76.7%) were in the category of low physical functional activity and 14 elderly people (23.3%) had good functional activity. The female elderly group consisted of 28 (75.7%) who had lower scores compared to male elderly. The 60-70 age group consisted of 30 elderly (78.9%) had a lower PASE score compared to the 71-80 age group. The housewife occupation group consisted of 22 elderly people (75.9%) had lower scores compared to the entrepreneur, laborer and retiree groups. The number of cases of decreased physical functional activity in the elderly is 46 individuals or 76.7%. The decline in physical functional activity was influenced by age, gender and occupation. To further explore the factors that influence the decline in physical functional activity.